2016
DOI: 10.1186/s12885-016-2228-y
|View full text |Cite
|
Sign up to set email alerts
|

Local iron homeostasis in the breast ductal carcinoma microenvironment

Abstract: BackgroundWhile the deregulation of iron homeostasis in breast epithelial cells is acknowledged, iron-related alterations in stromal inflammatory cells from the tumor microenvironment have not been explored.MethodsImmunohistochemistry for hepcidin, ferroportin 1 (FPN1), transferrin receptor 1 (TFR1) and ferritin (FT) was performed in primary breast tissues and axillary lymph nodes in order to dissect the iron-profiles of epithelial cells, lymphocytes and macrophages. Furthermore, breast carcinoma core biopsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 55 publications
1
64
1
1
Order By: Relevance
“…This is particularly relevant since it was appreciated that tumor cells are not able to acquire a fully invasive potential without the recruitment and the support of tumor-infiltrating immune cells, especially MΦ [5052]. Along this line, recent studies could show that lymphocytes and MΦ synthesize and secrete ferritin which, in turn, stimulates tumor cell proliferation in an iron-dependent manner [39, 5355]. These data reinforce the importance of the tumor microenvironment in terms of the iron-handling capacity of tumor-infiltrating immune cells, in particular MΦ.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant since it was appreciated that tumor cells are not able to acquire a fully invasive potential without the recruitment and the support of tumor-infiltrating immune cells, especially MΦ [5052]. Along this line, recent studies could show that lymphocytes and MΦ synthesize and secrete ferritin which, in turn, stimulates tumor cell proliferation in an iron-dependent manner [39, 5355]. These data reinforce the importance of the tumor microenvironment in terms of the iron-handling capacity of tumor-infiltrating immune cells, in particular MΦ.…”
Section: Discussionmentioning
confidence: 99%
“…D . Tissue iron stored as ferritin has found to be increased in MS271, AD272, PD264, AS259,273, and for cancer both high levels (glioblastoma)94 and low levels have been reported (breast)101. E .…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 98%
“…However, the additional intracellular oxidative stress that is accompanied by the increased presence of labile iron may also make them more sensitive to ferroptosis65,67 and hinder tumour metastasis85, illustrating the complex relationship between iron, ROS and cancer cell survival. Furthermore, although a connection between iron and cancer growth has been demonstrated in several forms of cancers, with breast cancer90,91,99101, prostate cancer98,102,103 and glioblastoma as established examples94,104, it seems reasonable that many, but not all, cancer types will demonstrate a similar iron dependency.…”
Section: Iron and The Pathophysiology Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that increased serum hepcidin was related to multiple cancers, such as breast cancer, myeloma, renal cell carcinoma and prostate cancer [7][8][9][10]. Hepcidin is homeostatically regulated by iron and erythropoietic activity as well as inflammatory cytokines [9,11]. Hepcidin inhibits iron absorption from the duodenum and iron egress from macrophages and hepatocytes through binding and inducing degradation of iron exporter ferroportin [12,13].…”
Section: Introductionmentioning
confidence: 99%